Eliminating financial disincentives to living kidney donation – a call to action - Polireddy, Karunesh; Crepeau, Rebecca L.; Matar, Abraham J. (Frontiers in Medicine, 2023)
The incidence of end stage renal disease (ESRD) in the United States (US) is increasing each year. The lone curative treatment for ESRD remains kidney transplantation. Despite the demonstrated medical and economic benefits, living donor kidney transplantation (LDKT) only accounts for a small number of kidney transplantations each year. Direct and indirect costs exist that disincentivize potential living kidney donors from coming forward, such as the cost of travel and lodging, risk of death, potential loss of income due to an extended recovery time, and the inability to donate to a relative in the future if needed. Herein, we advocate for policy changes that make living kidney donation (LKD) a financially neutral process thereby incentivizing increased LDKT and mitigating the kidney donor shortage.